1989
DOI: 10.1007/bf00616301
|View full text |Cite
|
Sign up to set email alerts
|

UV-excimer-laser ablation of polymethylmethacrylate at 248 nm: Characterization of incubation sites with Fourier transform IR- and UV-Spectroscopy

Abstract: Abstract. Ultraviolet and Fourier transform infrared (FTIR) spectroscopic experiments with thin films of polymethylmethacrylate (PMMA) are reported. During the incubation with 248 nm excimer laser light or continuous (cw) UV light sources PMMA exhibits a rapidly increasing, broad UV absorption. This is caused by the production of unsaturated species, which are detected in the infrared spectrum of irradiated PMMA films. The spectral data explain the incubation process preceding the ablation of PMMA at 248 nm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(53 citation statements)
references
References 18 publications
4
45
0
4
Order By: Relevance
“…Due to the complex nature of laser-polymer interactions, these novel structures are expected to have properties that are significantly different from the base material because of the defects generated during laser irradiation. These defects might have a physical origin due to a local increase in absorption [19] or a chemical origin due to preferential bond breaking [20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex nature of laser-polymer interactions, these novel structures are expected to have properties that are significantly different from the base material because of the defects generated during laser irradiation. These defects might have a physical origin due to a local increase in absorption [19] or a chemical origin due to preferential bond breaking [20].…”
Section: Introductionmentioning
confidence: 99%
“…These chromophores can increase absorption not only at the irradiating wavelength )~o but also at other wavelengths (usually on the long-wavelength side of 2 o), where the unirradiated polymer is essentially transparent. In UV laser experiments on relatively weakly absorbing polymers this steady growth in absorption can explain why there is a delay, in terms of number of pulses, before ablation commences, i.e., a so called incubation effect [1][2][3]. In these systems it has also been demonstrated that "incubated" absorption induced by short wavelength exposure can permit the subsequent ablation of the polymer at a longer laser wavelength and at a significantly lower fluence than tbr the unexposed case [3].…”
mentioning
confidence: 95%
“…[3][4][5] For example, Kueper and Stuke reported production of unsaturated species in irradiated poly(methyl methacrylate) films. 6 The wetting behavior of the irradiated polymer improves as a result, and the increased surface roughness due to ablation can be an important effect in enhancing adhesion. 7,8 Enhancement of polymer surface conductivity due to laser irradiation has also been reported.…”
Section: Introductionmentioning
confidence: 99%